Aqueous dispersion, method for producing the aqueous dispersion, and laminate
By using composite particles of ethylene-unsaturated carboxylic acid copolymer and acrylic polymer in the aqueous dispersion, the problem of insufficient polymerization and storage stability is solved, and the heat seal strength and adhesion resistance are improved, ensuring bonding The efficiency and durability of the agent layer.
Patent Information
- Application Number
- CN202180046795.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-14
- Filing Date
- 2021-07-13
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-07-13
AI Technical Summary
The existing aqueous dispersions have insufficient polymerization stability and storage stability during the manufacturing process, resulting in an adhesive layer with poor heat sealing strength.
Using composite particles containing ethylene-unsaturated carboxylic acid copolymer and acrylic polymer, an aqueous dispersion with excellent polymerization stability and storage stability is prepared by polymerization in the presence of a polymerization initiator, and a bonding is formed by drying. Conjugate layer.
It achieves excellent bonding strength and adhesion resistance during the heat sealing process, improves the polymerization and storage stability of the aqueous dispersion, and ensures the efficiency and durability of the adhesive layer.
Smart Images

Figure BDA0004027707610000341 
Figure BDA0004027707610000351 
Figure BDA0004027707610000381
Abstract
Description
Technical Field
[0001] The present invention relates to an aqueous dispersion, a method for producing the aqueous dispersion, and a laminate. Background Art
[0002] The method of bonding a substrate such as a plastic film, vapor-deposited film, metal foil, paper, non-woven fabric, etc., to another adherend or to each other by heat and pressure (i.e., heat sealing) has gradually been widely used in various industrial fields. In the heat sealing method, an adhesive layer that can be bonded by heat and pressure is usually provided on the substrate in advance, and the substrate and the other adherend, or the substrates are bonded to each other via the adhesive layer.
[0003] As a material that can be used in such heat sealing, for example, a water dispersion has been proposed, which comprises: composite particles having an ethylene-unsaturated carboxylic acid copolymer and a polymer containing an acrylic ester unit as a polymerization unit; and composite particles (E) having an ethylene-unsaturated carboxylic acid copolymer and the aforementioned ethylene-vinyl acetate copolymer (see, for example, Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2018 / 142997 Pamphlet Summary of the invention
[0007] Problems to be solved by the invention
[0008] The aqueous dispersion described in Patent Document 1 is a very excellent aqueous dispersion in that it is possible to obtain an adhesive layer having excellent adhesive strength even when the heat sealing time is short and the adhesive layer has excellent blocking resistance.
[0009] However, there may be problems with polymerization stability during the process of producing the aqueous dispersion and storage stability of the obtained aqueous dispersion.
[0010] The present invention aims to provide an aqueous dispersion which has excellent polymerization stability and storage stability during the production of the aqueous dispersion and can provide an adhesive layer having excellent heat seal strength, a method for producing the aqueous dispersion, and a laminate comprising an adhesive layer obtained from a coating of the aqueous dispersion and a substrate.
[0011] Means for solving problems
[0012] The inventors of the present application have conducted intensive studies and have found that the above-mentioned problems can be solved by a water dispersion having the following structure, etc., thereby completing the present invention. The structure of the present invention is as follows.
[0013] [1] an aqueous dispersion comprising a resin component and water,
[0014] The resin component comprises composite particles (D) having an ethylene-unsaturated carboxylic acid copolymer mixture (A) and an acrylic polymer (B),
[0015] The ethylene-unsaturated carboxylic acid copolymer mixture (A) includes two or more types of ethylene-unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids.
[0016] [2] An aqueous dispersion as described in item [1], wherein the total content of structural units derived from unsaturated carboxylic acid contained in the ethylene / unsaturated carboxylic acid copolymer in the aforementioned ethylene / unsaturated carboxylic acid copolymer mixture (A) is 5% by mass or more relative to the total amount of structural units derived from monomers in the polymer contained in the aforementioned mixture (A).
[0017] [3] The aqueous dispersion according to item [1] or [2], wherein the ethylene-unsaturated carboxylic acid copolymer mixture (A) comprises at least one of an ethylene-unsaturated carboxylic acid copolymer (a1) having a content of structural units derived from unsaturated carboxylic acid of 12% by mass to 30% by mass, and an ethylene-unsaturated carboxylic acid copolymer (a2) having a content of structural units derived from unsaturated carboxylic acid of less than 12% by mass,
[0018] The content of the ethylene-unsaturated carboxylic acid copolymer (a1) in the mixture (A) is 30% by mass or more and 90% by mass or less.
[0019] [4] The aqueous dispersion according to any one of items [1] to [3], wherein the content of the ethylene-unsaturated carboxylic acid copolymer mixture (A) in the composite particles (D) is 20% by mass or more and 80% by mass or less, and the content of the acrylic polymer (B) is 20% by mass or more and 80% by mass or less (wherein the total amount of (A) and (B) is 100% by mass).
[0020] [5] The aqueous dispersion according to any one of items [1] to [4], wherein the ethylene-unsaturated carboxylic acid copolymer mixture (A) further comprises an olefin polymer (c),
[0021] The total content of the ethylene-unsaturated carboxylic acid copolymer in the mixture (A) is 60% by mass or more.
[0022] [6] An aqueous dispersion as described in item [5], wherein the above-mentioned olefin-based polymer (c) comprises at least one polymer selected from the group consisting of low-density polyethylene, ethylene·1-butene copolymer, ethylene·propylene copolymer, ethylene·1-butene·propylene copolymer, ethylene·propylene·ethylidene norbornene copolymer, ethylene·(meth)acrylate copolymer, ethylene·(meth)acrylate·unsaturated carboxylic acid copolymer, ethylene·vinyl acetate copolymer, and ethylene·vinyl acetate·carbon monoxide copolymer.
[0023] [7] A method for producing the aqueous dispersion according to any one of items [1] to [6], comprising the following steps:
[0024] A step of emulsifying an ethylene-unsaturated carboxylic acid copolymer mixture (A) containing two or more ethylene-unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids in the presence of water to obtain a dispersion 1; and
[0025] A step of adding a monomer containing a (meth)acrylic acid ester to the above-mentioned dispersion 1 in the presence of a polymerization initiator to polymerize the acrylic polymer (B) to obtain a dispersion 2 containing composite particles (D) having an ethylene-unsaturated carboxylic acid copolymer mixture (A) and the acrylic polymer (B).
[0026] [8] A laminate comprising a substrate and an adhesive layer laminated on at least one surface of the substrate,
[0027] The adhesive layer is obtained by drying a coating of the aqueous dispersion according to any one of items [1] to [6].
[0028] [9] The laminate according to item [8], further comprising an adherend layer to be laminated on the surface of the adhesive layer opposite to the surface in contact with the substrate.
[0029]
[10] The laminate according to item [8] or [9], wherein the substrate is a plastic film, a vapor-deposited film, a metal foil, paper, or a nonwoven fabric.
[0030]
[11] The laminate according to item [9] or
[10] , wherein the adherend layer is a plastic film, a vapor-deposited film, a metal foil, paper, or a nonwoven fabric.
[0031]
[12] The laminate according to any one of items [9] to
[11] , wherein the adherend layer is a plastic film obtained from polyvinyl chloride, polyvinylidene chloride, or a mixture thereof.
[0032]
[13] A laminate comprising a substrate and an adhesive layer laminated on at least one surface of the substrate, wherein the adhesive layer comprises composite particles (D) comprising an ethylene-unsaturated carboxylic acid copolymer mixture (A) and an acrylic polymer (B),
[0033] The ethylene-unsaturated carboxylic acid copolymer mixture (A) includes two or more types of ethylene-unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids.
[0034] Effects of the Invention
[0035] According to the present invention, there are obtained an aqueous dispersion which has excellent polymerization stability and storage stability during the process of producing the aqueous dispersion and can produce an adhesive layer with excellent heat sealing strength, a method for producing the aqueous dispersion, a laminate having an adhesive layer obtained from a coating of the aqueous dispersion and a substrate, and the like. DETAILED DESCRIPTION
[0036] In the present specification, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0037] In the numerical ranges described in stages in the present specification, the upper limit value or the lower limit value described in one numerical range may be replaced with the upper limit value or the lower limit value of another numerical range described in stages.
[0038] The water dispersion of the present invention contains a resin component and water for dispersing the resin component.
[0039] The resin component comprises composite particles (D) comprising an ethylene-unsaturated carboxylic acid copolymer mixture (A) and an acrylic polymer (B). However, the ethylene-unsaturated carboxylic acid copolymer mixture (A) does not contain the acrylic polymer (B).
[0040] <Ethylene·Unsaturated Carboxylic Acid Copolymer Mixture (A)>
[0041] The ethylene-unsaturated carboxylic acid copolymer mixture (A) contains two or more types of ethylene-unsaturated carboxylic acid copolymers having different contents of the structural unit derived from the unsaturated carboxylic acid.
[0042] [Ethylene·unsaturated carboxylic acid copolymer]
[0043] The two or more ethylene-unsaturated carboxylic acid copolymers contained in the mixture (A) are each obtained by polymerizing a monomer component (a′) containing ethylene and an unsaturated carboxylic acid.
[0044] Unsaturated carboxylic acids are monomers having at least one ethylenically unsaturated bond and a carboxyl group. Examples of the unsaturated carboxylic acids include monobasic acids having ethylenically unsaturated bonds such as acrylic acid, methacrylic acid, and crotonic acid; dibasic acids having ethylenically unsaturated bonds such as maleic acid, fumaric acid, and itaconic acid; and the like.
[0045] These unsaturated carboxylic acids may be used alone or in combination of two or more.
[0046] Among the unsaturated carboxylic acids described above, monobasic acids having an ethylenically unsaturated bond are preferred from the viewpoint of water resistance, and acrylic acid and methacrylic acid are more preferred.
[0047] The content ratio of ethylene in the monomer component (a') can be appropriately set according to the content of the structural unit derived from ethylene in the obtained ethylene-unsaturated carboxylic acid copolymer. Similarly, the content ratio of the unsaturated carboxylic acid in the monomer component (a') can be appropriately set according to the content of the structural unit derived from the unsaturated carboxylic acid in the ethylene-unsaturated carboxylic acid copolymer.
[0048] There are no particular restrictions on the polymerization method of the monomer component (a') as long as the desired ethylene-unsaturated carboxylic acid copolymer can be obtained. Examples of the polymerization method include known polymerization methods. The ethylene-unsaturated carboxylic acid copolymer can be obtained, for example, by contacting the monomer component (a') with a polymerization initiator such as a peroxide under high temperature and high pressure conditions and polymerizing.
[0049] In addition, the ethylene·unsaturated carboxylic acid copolymer can be obtained as an aqueous dispersion (dispersion) in which its polymer particles (resin component) are dispersed in water. In such a case, the monomer component (a') can be polymerized by the method described in, for example, Japanese Patent Publication No. 7-008933, Japanese Patent Publication No. 5-039975, Japanese Patent Publication No. 4-030970, Japanese Patent Publication No. 42-000275, Japanese Patent Publication No. 42-023085, Japanese Patent Publication No. 45-029909, Japanese Patent Publication No. 51-062890, etc. It should be noted that the ethylene·unsaturated carboxylic acid copolymer has self-emulsification.
[0050] Furthermore, when polymerizing the ethylene-unsaturated carboxylic acid copolymer, an emulsifier (surfactant) described below may be added as needed from the viewpoint of improving polymerization stability. The addition ratio of the emulsifier may be appropriately set according to the purpose and application.
[0051] In addition, when polymerizing into an ethylene-unsaturated carboxylic acid copolymer, from the viewpoint of improving polymerization stability, additives such as pH adjusters, metal ion sealants (such as ethylenediaminetetraacetic acid or its salts), molecular weight regulators (also known as chain transfer agents; for example, thiols, low molecular weight halides) may be added.
[0052] Furthermore, from the viewpoint of achieving improved polymerization stability during the production process of the composite particles (D) and improved storage stability, the ethylene / unsaturated carboxylic acid copolymer contained in the ethylene / unsaturated carboxylic acid copolymer mixture (A) is preferably neutralized before use.
[0053] Neutralization is performed, for example, by adding a basic compound as a neutralizing agent to the ethylene-unsaturated carboxylic acid copolymer. For example, neutralization can be performed by adding a basic compound as a neutralizing agent to the aqueous dispersion of the ethylene-unsaturated carboxylic acid copolymer.
[0054] Examples of the basic compound used as the neutralizing agent include inorganic basic compounds such as sodium hydroxide and potassium hydroxide; organic basic compounds represented by amines such as ammonia, triethylamine, triethanolamine, and dimethylethanolamine; and the like.
[0055] These basic compounds may be used alone or in combination of two or more.
[0056] Among these basic compounds, inorganic basic compounds are preferred, and sodium hydroxide is more preferred.
[0057] From the viewpoint of achieving improved polymerization stability during the production process of the composite particles (D) and improved storage stability, the amount of the basic compound added is, for example, 5 mol or more, preferably 30 mol or more, more preferably 50 mol or more, for example, 200 mol or less, preferably 150 mol or less, relative to 100 mol of carboxyl groups contained in the entire ethylene·unsaturated carboxylic acid copolymer contained in the ethylene·unsaturated carboxylic acid copolymer mixture (A).
[0058] When the amount of the basic compound added is less than the above range, the polymerization stability when preparing the composite particles (D) or the storage stability of the composite particles (D) may be impaired. In addition, when the amount of the basic compound added exceeds the above range, the viscosity of the obtained aqueous dispersion may be increased or the operability of the aqueous dispersion may be reduced.
[0059] Furthermore, after the neutralizing agent is added to the ethylene-unsaturated carboxylic acid copolymer for neutralization, it is preferred to maintain the copolymer at a predetermined temperature for a predetermined time.
[0060] The holding condition includes a holding temperature of, for example, 40° C. or higher, preferably 50° C. or higher, for example, 190° C. or lower, preferably 180° C. or lower. The holding time is, for example, 30 minutes or higher, preferably 1 hour or higher, for example, 12 hours or lower, preferably 10 hours or lower.
[0061] By maintaining the above conditions, the carboxyl groups contained in the ethylene-unsaturated carboxylic acid copolymer are reliably neutralized, and the polymerization stability in the production process of the composite particles (D) and the storage stability of the composite particles (D) can be improved.
[0062] When the ethylene·unsaturated carboxylic acid copolymer contained in the ethylene·unsaturated carboxylic acid copolymer mixture (A) is neutralized, the degree of neutralization of the ethylene·unsaturated carboxylic acid copolymer is, for example, 20% or more, preferably 50% or more, for example, 200% or less, preferably 150% or less, based on the total amount of the two or more ethylene·unsaturated carboxylic acid copolymers. The degree of neutralization herein refers to the molar percentage of carboxyl groups contained in the total amount of the ethylene·unsaturated carboxylic acid copolymer neutralized by the basic compound as a neutralizing agent.
[0063] When the degree of neutralization is within the above range, an adhesive layer having excellent heat seal strength can be obtained from the aqueous dispersion of the present invention. The degree of neutralization is calculated according to the Examples described below.
[0064] The weight average molecular weight of each ethylene-unsaturated carboxylic acid copolymer contained in the ethylene-unsaturated carboxylic acid copolymer mixture (A) is, for example, 10,000 or more, preferably 30,000 or more, for example, 200,000 or less, preferably 150,000 or less, in terms of standard polystyrene measured by gel permeation chromatography (GPC).
[0065] The melting point of each ethylene-unsaturated carboxylic acid copolymer contained in the ethylene-unsaturated carboxylic acid copolymer mixture (A) is, for example, 55° C. or higher, preferably 65° C. or higher, for example, 110° C. or lower, preferably 100° C. or lower. The melting point can be determined by DSC (differential scanning calorimetry).
[0066] The ethylene·unsaturated carboxylic acid copolymer mixture (A) comprises two or more ethylene·unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids. By using the ethylene·unsaturated carboxylic acid copolymer (a) with two or more ethylene·unsaturated carboxylic acid copolymers, the polymerization stability during the production process of the composite particles (D) is improved, and the storage stability of the composite particles (D) is improved.
[0067] As two or more ethylene·unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids contained in the ethylene·unsaturated carboxylic acid copolymer mixture (A), it is preferred to contain at least one ethylene·unsaturated carboxylic acid copolymer (a1) having a content of structural units derived from unsaturated carboxylic acids of 12% by mass to 30% by mass, and at least one ethylene·unsaturated carboxylic acid copolymer (a2) having a content of structural units derived from unsaturated carboxylic acids of less than 12% by mass. By using at least one ethylene·unsaturated carboxylic acid copolymer (a1) and (a2) as the ethylene·unsaturated carboxylic acid copolymer (a), the polymerization stability in the production process of the composite particles (D) is further improved, and the storage stability of the aqueous dispersion containing the composite particles (D) is further improved.
[0068] From the viewpoint of promoting the polymerization stability during the production process of the composite particles (D) or improving the storage stability of the composite particles (D), the content of the structural unit derived from the unsaturated carboxylic acid in the ethylene-unsaturated carboxylic acid copolymer (a1) is preferably 12% by mass or more, more preferably 15% by mass or more, preferably 30% by mass or less, more preferably 25% by mass or less.
[0069] The weight average molecular weight of the ethylene-unsaturated carboxylic acid copolymer (a1) is, for example, 10,000 or more, preferably 30,000 or more, and for example, 200,000 or less, preferably 150,000 or less, in terms of standard polystyrene measured by GPC.
[0070] The melting point of the ethylene-unsaturated carboxylic acid copolymer (a1) is, for example, 55°C or higher, preferably 65°C or higher, and for example, 110°C or lower, preferably 100°C or lower.
[0071] From the viewpoint of promoting the polymerization stability during the production process of the composite particles (D) or improving the storage stability of the composite particles (D), the content of the structural unit derived from the unsaturated carboxylic acid in the ethylene-unsaturated carboxylic acid copolymer (a2) is preferably 1% by mass or more, more preferably 5% by mass or more, preferably less than 12% by mass, more preferably less than 11% by mass.
[0072] The weight average molecular weight of the ethylene-unsaturated carboxylic acid copolymer (a2) is, for example, 10,000 or more, preferably 30,000 or more, and for example, 200,000 or less, preferably 150,000 or less, in terms of standard polystyrene measured by GPC.
[0073] The melting point of the ethylene-unsaturated carboxylic acid copolymer (a2) is, for example, 55°C or higher, preferably 65°C or higher, and for example, 110°C or lower, preferably 100°C or lower.
[0074] From the viewpoint of promoting the polymerization stability during the production process of the composite particles (D) or improving the storage stability of the composite particles (D), the total content (average value of the content) of the structural units derived from the unsaturated carboxylic acid contained in the ethylene-unsaturated carboxylic acid copolymer in the above-mentioned ethylene-unsaturated carboxylic acid copolymer mixture (A) is preferably 5% by mass or more, more preferably 8% by mass or more, and preferably 30% by mass or less, more preferably 25% by mass or less, relative to the total amount of the structural units derived from the monomers of the polymer contained in the above-mentioned mixture (A). The total content (average value of the content) of the structural units derived from the unsaturated carboxylic acid can be obtained by neutralization titration.
[0075] From the viewpoint of promoting the polymerization stability during the production process of the composite particles (D) or improving the storage stability of the composite particles (D) and improving the water resistance of the obtained coating film, the content of the structural units derived from ethylene contained in the ethylene·unsaturated carboxylic acid copolymer (a) in the aforementioned ethylene·unsaturated carboxylic acid copolymer mixture (A) is preferably 70% by mass or more, more preferably 75% by mass or more, and preferably 95% by mass or less, more preferably 92% by mass or less, relative to the total amount of the structural units derived from the monomers of the polymer contained in the aforementioned mixture (A).
[0076] The content of each of the two or more ethylene / unsaturated carboxylic acid copolymers contained in the ethylene / unsaturated carboxylic acid copolymer mixture (A) is not particularly limited as long as the effects of the present invention are not impaired.
[0077] For example, when the ethylene·unsaturated carboxylic acid copolymer (a1) and the ethylene·unsaturated carboxylic acid copolymer (a2) are contained as the ethylene·unsaturated carboxylic acid copolymer mixture (A), from the viewpoint of promoting the polymerization stability in the production process of the composite particles (D) or improving the storage stability of the composite particles (D), the content of the ethylene·unsaturated carboxylic acid copolymer (a1) in the mixture (A) is preferably 30% by mass or more, more preferably 40% by mass or more, preferably 90% by mass or less, and more preferably 80% by mass or less. In addition, in the above case, the content of the ethylene·unsaturated carboxylic acid copolymer (a2) in the mixture (A) is preferably 10% by mass or more, more preferably 20% by mass or more, preferably 70% by mass or less, and more preferably 60% by mass or less.
[0078] In order to include two or more ethylene·unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids as an ethylene·unsaturated carboxylic acid copolymer mixture (A), the method for preparing the mixture of these copolymers is not particularly limited. For example, the above-mentioned mixture can be prepared by melt-kneading two or more of the above-mentioned copolymers at a melting point above the melting point of the ethylene·unsaturated carboxylic acid copolymer with the highest melting point contained in the ethylene·unsaturated carboxylic acid copolymer mixture (A), preferably above 150°C. In addition, when each ethylene·unsaturated carboxylic acid copolymer is obtained as an aqueous dispersion containing an ethylene·unsaturated carboxylic acid copolymer as described above, these aqueous dispersions can be heated and pressurized as needed, and mixed to prepare an aqueous dispersion containing the above-mentioned mixture (A).
[0079] When the ethylene·unsaturated carboxylic acid copolymer is used in the form of a substance obtained by neutralizing the ethylene·unsaturated carboxylic acid copolymer as described above, it can be prepared, for example, in the following manner: melt-kneading two or more ethylene·unsaturated carboxylic acid copolymers as described above to prepare a melt-kneaded product, and the obtained melt-kneaded product is put into an aqueous solution containing a neutralizer and water (which is preferably maintained at a melting point of the ethylene·unsaturated carboxylic acid copolymer with the highest melting point, more preferably at a melting point of 150°C or more, and further preferably at a melting point of 170°C or more), and they are mixed. The specific example and addition amount of the neutralizer, as well as the holding conditions during mixing, are the same as those described in the section on the preparation of the substance obtained by neutralizing the ethylene·unsaturated carboxylic acid copolymer. It should be noted that the ethylene·unsaturated carboxylic acid copolymer has self-emulsification properties, so the amount of the emulsifier (surfactant) can be reduced. If the amount of the emulsifier is large, it sometimes affects the adhesion.
[0080] The weight average molecular weight of the two or more ethylene-unsaturated carboxylic acid copolymers contained in the ethylene-unsaturated carboxylic acid copolymer mixture (A) as a whole is, for example, 10,000 or more, preferably 30,000 or more, for example, 200,000 or less, preferably 150,000 or less, in terms of standard polystyrene measured by gel permeation chromatography (GPC).
[0081] The melting point of the two or more ethylene / unsaturated carboxylic acid copolymers contained in the ethylene / unsaturated carboxylic acid copolymer mixture (A) as a whole is, for example, 55°C or higher, preferably 65°C or higher, for example, 110°C or lower, preferably 100°C or lower.
[0082] The average content of the monomer units derived from unsaturated carboxylic acid in the total of two or more ethylene-unsaturated carboxylic acid copolymers contained in the ethylene-unsaturated carboxylic acid copolymer mixture (A) is, for example, 8 mass % or more, preferably 10 mass % or more, for example, 25 mass % or less, preferably 22 mass % or less.
[0083] The average content of monomer units derived from ethylene in the two or more ethylene-unsaturated carboxylic acid copolymers contained in the ethylene-unsaturated carboxylic acid copolymer mixture (A) is, for example, 75% by mass or more, preferably 78% by mass or more, for example, 92% by mass or less, preferably 90% by mass or less. The average content of monomer units derived from unsaturated carboxylic acids and the average content of monomer units derived from ethylene are determined using a Fourier transform infrared spectrophotometer (FT-IR).
[0084] [Olefin polymer (c)]
[0085] The ethylene-unsaturated carboxylic acid copolymer mixture (A) may further contain an olefin polymer (c). The olefin polymer (c) herein refers to a polymer having a structural unit derived from an olefin (c'-1). However, the ethylene-unsaturated carboxylic acid copolymer is not included in the olefin polymer (c).
[0086] Examples of the olefin polymer (c) include the following olefin polymers (c1) to (c3).
[0087] (1) An olefin polymer (c1) formed by polymerizing only an olefin (c'-1).
[0088] (2) An olefin polymer (c2) formed by polymerizing an olefin (c'-1) and a monomer (c'-3) copolymerizable with the olefin (c'-1) other than the carboxyl group-containing monomer (c'-2).
[0089] (3) An olefin polymer (c3) formed by polymerizing an olefin (c'-1), a carboxyl group-containing monomer (c'-2), and a monomer (c'-3) copolymerizable with the olefin (c'-1) other than the carboxyl group-containing monomer (c'-2). The ethylene-unsaturated carboxylic acid copolymer (a) is not included in the olefin polymer (c3).
[0090] Examples of the olefin (c'-1) include α-olefins such as ethylene, propylene, 1-butene, 3-methyl-1-butene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-hexene, 1-decene, and 1-dodecene; and conjugated dienes or non-conjugated dienes such as butadiene, ethylidene norbornene, dicyclopentadiene, and 1,5-hexadiene. These olefins may be used alone or in combination of two or more.
[0091] As the aforementioned carboxyl-containing monomer (c'-2), for example, (meth)acrylic acid, maleic acid, itaconic acid, crotonic acid, and fumaric acid can be cited. Among them, acrylic acid and methacrylic acid are preferred from the viewpoint of improving heat sealability. These monomers (c'-2) can be used alone or in combination of two or more. It should be noted that (meth)acrylic acid refers to acrylic acid and / or methacrylic acid.
[0092] As the aforementioned monomer (c'-3), that is, the monomer copolymerizable with the olefin (c'-1) other than the carboxyl-containing monomer (c'-2), for example, vinyl acetate, vinyl alcohol, (meth)acrylate, carbon monoxide can be cited. Among them, from the viewpoint of improving the heat sealability of the obtained composite particles (D), vinyl acetate, (meth)acrylate, and carbon monoxide are preferred. These monomers (c'-3) can be used alone or in combination of two or more. It should be noted that the so-called (meth)acrylate refers to acrylate and / or methacrylate. Similarly, (meth)propylene- refers to propylene- and / or methpropylene-, and (meth)acrylate refers to acrylate and / or methacrylate.
[0093] [Ratio of olefin (c'-1) / monomer (c'-2) / monomer (c'-3)]
[0094] The ratio of olefin (c'-1), monomer (c'-2) and monomer (c'-3) is preferably set as follows. That is, when the total amount of olefin (c'-1), carboxyl group-containing monomer (c'-2) and monomer (c'-3) is set to 100% by mass,
[0095] Preferably, the olefin (c'-1) is 100 to 35.0 mass %, the carboxyl group-containing monomer (c'-2) is 0 to 65.0 mass %, and the monomer (c'-3) is 0 to 50.0 mass %.
[0096] More preferably, the olefin (c'-1) is 100 to 50.0 mass%, the carboxyl group-containing monomer (c'-2) is 0 to 50.0 mass%, and the monomer (c'-3) is 0 to 40.0 mass%. If the olefin (c'-1) is less than 35.0 mass%, the heat sealability may be reduced.
[0097] As the aforementioned olefin-based polymer (c1), there can be mentioned low-density polyethylene, high-density polyethylene, polypropylene, poly-1-butene, poly-3-methyl-1-butene, poly-4-methyl-1-pentene, poly-3-methyl-1-pentene; homopolymers or copolymers of α-olefins having more than 1 carbon atom number, such as ethylene·propylene copolymer, ethylene·1-butene copolymer, propylene·1-butene copolymer, ethylene·1-butene·propylene copolymer, propylene·1-butene·ethylene copolymer, etc.
[0098] Examples of the aforementioned olefin-based polymer (c2) include copolymers of α-olefins having 1 or more carbon atoms and conjugated dienes or non-conjugated dienes, such as ethylene·butadiene copolymers, ethylene·ethylidene norbornene copolymers, ethylene·propylene·butadiene copolymers, ethylene·propylene·dicyclopentadiene copolymers, ethylene·propylene·ethylidene norbornene copolymers, and ethylene·propylene·1,5-hexadiene copolymers; and copolymers of α-olefins having 1 or more carbon atoms and other monomers copolymerizable with α-olefins having 1 or more carbon atoms, such as ethylene·(meth)acrylate copolymers, ethylene·vinyl acetate copolymers, ethylene·vinyl acetate·carbon monoxide copolymers, and ethylene·vinyl alcohol copolymers.
[0099] For example, when the adherend is a material obtained from polyvinyl chloride, polyvinylidene chloride, or a mixture thereof, from the viewpoint of improving the heat sealability of the composite particles (D), among the olefin polymers (c), preferred are low-density polyethylene, ethylene·1-butene copolymers, ethylene·propylene copolymers, ethylene·1-butene·propylene copolymers, ethylene·propylene·ethylidene norbornene copolymers, ethylene·(meth)acrylate copolymers, ethylene·(meth)acrylate·unsaturated carboxylic acid copolymers, ethylene·vinyl acetate copolymers, and ethylene·vinyl acetate·carbon monoxide copolymers.
[0100] When an ethylene-vinyl acetate copolymer is used as the olefin polymer (c), the content of the structural unit derived from ethylene in the ethylene-vinyl acetate copolymer is preferably 50 to 95% by mass, and the content of the structural unit derived from vinyl acetate is preferably 5 to 50% by mass.
[0101] In the ethylene-vinyl acetate copolymer, the content of the structural unit derived from ethylene is preferably 52% by mass or more, more preferably 54% by mass or more, preferably 90% by mass or less, more preferably 85% by mass or less, and from the viewpoint of improving the bonding strength of the composite particles (D), it is further preferably 80% by mass or less. In the ethylene-vinyl acetate copolymer, the content of the structural unit derived from vinyl acetate is preferably 10% by mass or more, more preferably 15% by mass or more, and from the viewpoint of improving the bonding strength of the composite particles (D), it is further preferably 20% by mass or more, preferably 48% by mass or less, and more preferably 46% by mass or less.
[0102] When the copolymerization ratio of ethylene to vinyl acetate is within the above range, the composite particles (D) tend to be excellent in low-temperature heat-sealing properties.
[0103] In the ethylene-vinyl acetate-carbon monoxide copolymer, the content of the structural unit derived from carbon monoxide is preferably 2 to 40% by mass, more preferably 5 to 30% by mass, based on the total amount of the structural units derived from the monomers contained in the copolymer.
[0104] The MFR (melt flow rate) (190° C., 2.16 kg load) of the ethylene-vinyl acetate copolymer is preferably 2 to 1000 g / 10 min, more preferably 5 to 500 g / 10 min.
[0105] The olefin polymer (c) may be used alone or in combination of two or more.
[0106] When the olefin polymer (c) is included, the ethylene-unsaturated carboxylic acid copolymer is integrated with an ethylene-unsaturated carboxylic acid copolymer containing two or more ethylene-unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids to form an ethylene-unsaturated carboxylic acid copolymer mixture (A). In this case, as long as the above two or more ethylene-unsaturated carboxylic acid copolymers and the olefin polymer (c) are included, the form of the ethylene-unsaturated carboxylic acid copolymer mixture (A) is not particularly limited, and for example, any structure such as a core / shell structure, a composite structure, a localized structure, a spherical structure, an octopus-like structure, a raspberry-like structure, a multi-particle composite structure, and an IPN structure may be used.
[0107] The method for producing the ethylene-unsaturated carboxylic acid copolymer mixture (A) containing the olefin polymer (c) is not particularly limited, and the ethylene-unsaturated carboxylic acid copolymer mixture (A) containing the olefin polymer (c) can be produced by, for example, a known production method. For example, the mixture can be produced by melt-kneading a plurality of polymers contained as components of the mixture (A) at a temperature above the melting point of the polymer with the highest melting point contained in the ethylene-unsaturated carboxylic acid copolymer mixture (A), preferably at a temperature above 150°C.
[0108] When each polymer is obtained as an aqueous dispersion containing the polymer, these aqueous dispersions may be heated and pressurized as necessary and mixed to prepare an aqueous dispersion containing the mixture (A).
[0109] In addition, an ethylene·unsaturated carboxylic acid copolymer (a) and an olefin polymer (c) containing two or more ethylene·unsaturated carboxylic acid copolymers can also be emulsified simultaneously to prepare an aqueous dispersion containing an ethylene·unsaturated carboxylic acid copolymer mixture (A). Specifically, it can be prepared by melt-kneading two or more ethylene·unsaturated carboxylic acid copolymers as described above to prepare a melt-kneaded product, and the obtained melt-kneaded product is put into water (which is preferably maintained at a melting point of the ethylene·unsaturated carboxylic acid copolymer with the highest melting point, preferably at a temperature of 150°C or more, and more preferably at a temperature of 170°C or more) and mixed. It should be noted that when the ethylene·unsaturated carboxylic acid copolymer is used in the form of a substance obtained by neutralizing the ethylene·unsaturated carboxylic acid copolymer as described above, it can be prepared by putting the obtained melt-kneaded product into an aqueous solution containing a neutralizer and water (which is preferably maintained at a temperature above the above) and mixing them. The specific example and amount of the neutralizer, as well as the holding conditions during mixing, are the same as those described in the preparation of the substance obtained by neutralizing the ethylene·unsaturated carboxylic acid copolymer.
[0110] In addition, as an olefin-based polymer (c), a commercially available product may be used.
[0111] When the ethylene·unsaturated carboxylic acid copolymer mixture (A) contains the olefin polymer (c), the content of the olefin polymer (c) is, for example, 1% by mass or more, preferably 5% by mass or more, more preferably 10% by mass or more, for example, 95% by mass or less, preferably 70% by mass or less, and more preferably less than 40% by mass, relative to the total amount of the ethylene·unsaturated carboxylic acid copolymer and the olefin polymer (c). In addition, the total content of the ethylene·unsaturated carboxylic acid copolymer is, for example, 5% by mass or more, preferably 30% by mass or more, more preferably 60% by mass or more, for example, 99% by mass or less, preferably 95% by mass or less, and more preferably 90% by mass or less, relative to the total amount of the ethylene·unsaturated carboxylic acid copolymer and the olefin polymer (c).
[0112] When the contents of the ethylene-unsaturated carboxylic acid copolymer and the olefin polymer (c) are within the above ranges, composite particles (D) having excellent adhesive strength can be obtained.
[0113] When the ethylene-unsaturated carboxylic acid copolymer mixture (A) contains the olefin polymer (c), the total amount of the ethylene-unsaturated carboxylic acid copolymer and the content of the olefin polymer (c) can be calculated from the charging ratio of the raw material components.
[0114] When the ethylene-unsaturated carboxylic acid copolymer mixture (A) is obtained as an aqueous dispersion, the weight average particle size of particles formed from the resin component thereof (measurement method: light scattering measurement) is, for example, 0.01 μm or more, preferably 0.02 μm or more, for example, 10 μm or less, preferably 1 μm or less.
[0115] When the ethylene-unsaturated carboxylic acid copolymer mixture (A) is obtained as an aqueous dispersion, the solid content concentration (concentration of non-volatile components such as the ethylene-unsaturated carboxylic acid copolymer) in the aqueous dispersion is, for example, 10 mass % or more, preferably 20 mass % or more, for example, 60 mass % or less, preferably 50 mass % or less.
[0116] <Acrylic polymer (B)>
[0117] The acrylic polymer (B) is a polymer obtained by polymerizing a monomer containing a (meth)acrylic acid ester, and has a structural unit derived from the (meth)acrylic acid ester.
[0118] Examples of the (meth)acrylate include (meth)acrylates having an alkyl group having 1 to 12 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate.
[0119] Among these (meth)acrylates, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, methyl (meth)acrylate and n-butyl (meth)acrylate are more preferred, and methyl methacrylate, n-butyl methacrylate, and butyl acrylate are further preferred.
[0120] Moreover, among the above-mentioned (meth)acrylates, it is desirable to use methacrylate from the viewpoint of water resistance.
[0121] These (meth)acrylates may be used alone or in combination of two or more.
[0122] The acrylic polymer (B) may contain a structural unit derived from a monomer copolymerizable with a (meth)acrylic acid ester.
[0123] Examples of the monomer copolymerizable with the (meth)acrylate include functional group-containing vinyl monomers, vinyl esters, aromatic vinyl monomers, N-substituted unsaturated carboxylic acid amides, heterocyclic vinyl compounds, vinylidene halide compounds, α-olefins, and dienes.
[0124] Examples of the functional group-containing vinyl monomer include carboxyl group-containing vinyl monomers, hydroxyl group-containing vinyl monomers, amino group-containing vinyl monomers, glycidyl group-containing vinyl monomers, cyano group-containing vinyl monomers, sulfonic acid group-containing vinyl monomers and salts thereof, acetoacetoxy group-containing vinyl monomers, phosphoric acid group-containing compounds, amide group-containing vinyl monomers, and the like.
[0125] Examples of the carboxyl group-containing vinyl monomer include (meth)acrylic acid, maleic anhydride, maleic acid, fumaric acid, itaconic acid, and crotonic acid.
[0126] As a hydroxyl group-containing vinyl monomer, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, etc. are mentioned, for example.
[0127] Examples of the amino group-containing vinyl monomer include 2-aminoethyl (meth)acrylate, 2-(N-methylamino)ethyl (meth)acrylate, and 2-(N,N-dimethylamino)ethyl (meth)acrylate.
[0128] Examples of the glycidyl group-containing vinyl monomer include glycidyl (meth)acrylate and the like.
[0129] Examples of the cyano group-containing vinyl monomer include acrylonitrile and methacrylonitrile.
[0130] Examples of the sulfonic acid group-containing vinyl monomer include allylsulfonic acid and methacrylic acid. Examples of salts thereof include alkali metal salts such as sodium salts and potassium salts of the above-mentioned sulfonic acid group-containing vinyl monomers, and ammonium salts. Specifically, examples of the salts of the sulfonic acid group-containing vinyl monomer include sodium allylsulfonate, sodium methacrylic sulfonate, and ammonium methacrylic sulfonate.
[0131] As an acetoacetoxy group-containing vinyl monomer, acetoacetoxyethyl (meth)acrylate etc. are mentioned, for example.
[0132] Examples of the phosphoric acid group-containing compound include 2-methacryloyloxyethyl acid phosphate.
[0133] Examples of the amide group-containing vinyl monomer include acrylamide and methacrylamide.
[0134] Examples of the vinyl esters include vinyl propionate (excluding vinyl acetate).
[0135] Examples of the aromatic vinyl monomer include styrene and α-methylstyrene.
[0136] Examples of the N-substituted unsaturated carboxylic acid amide include N-methylol acrylamide and N-methylol methacrylamide.
[0137] Examples of the heterocyclic vinyl compound include vinyl pyrrolidone and the like.
[0138] Examples of the vinylidene halide compound include vinylidene chloride and vinylidene fluoride.
[0139] Examples of the α-olefins include ethylene and propylene.
[0140] Examples of the dienes include butadiene and the like.
[0141] As the monomer copolymerizable with the (meth)acrylate, a crosslinkable vinyl monomer can be used.
[0142] Examples of the crosslinkable vinyl monomer include compounds containing two or more vinyl groups, such as methylenebisacrylamide, methylenebismethacrylamide, divinylbenzene, and di(meth)acrylate containing a polyethylene glycol chain.
[0143] Among the monomers copolymerizable with the (meth)acrylate, an aromatic vinyl monomer is preferred, and styrene is more preferred.
[0144] These monomers copolymerizable with (meth)acrylate may be used alone or in combination of two or more.
[0145] In the acrylic polymer (B), the content ratio of the structural unit derived from the (meth)acrylic acid ester relative to the total amount of the structural unit derived from the monomer is, for example, 40% by mass or more, preferably 70% by mass or more, more preferably 77% by mass or more, for example, 100% by mass or less. In the acrylic polymer (B), the content ratio of the structural unit derived from the monomer copolymerizable with the (meth)acrylic acid ester relative to the total amount of the structural unit derived from the monomer is, for example, 60% by mass or less, preferably 30% by mass or less, more preferably 23% by mass or less, for example, 0% by mass or more.
[0146] When the content of the structural unit derived from the (meth)acrylate ester and the structural unit derived from the monomer copolymerizable with the (meth)acrylate ester is within the above range, composite particles (D) having excellent adhesive strength and blocking resistance can be obtained.
[0147] That is, the acrylic polymer (B) may contain only the structural unit derived from (meth)acrylate, or may contain the structural unit derived from (meth)acrylate and the structural unit derived from the monomer copolymerizable with (meth)acrylate. Preferably, the acrylic polymer (B) contains only the structural unit derived from (meth)acrylate, or contains the structural unit derived from (meth)acrylate and the structural unit derived from the monomer copolymerizable with (meth)acrylate in the above-mentioned content ratio.
[0148] In addition, when a carboxyl group-containing vinyl monomer is used as a monomer copolymerizable with (meth)acrylate, from the viewpoint of manufacturing stability of the composite particles (D), the content ratio of the structural unit derived from the carboxyl group-containing vinyl monomer in the acrylic polymer (B) is, for example, 5% by mass or less, preferably 3% by mass or less relative to the total amount of the structural unit derived from the monomer. It should be noted that the acrylic polymer (B) preferably does not contain a structural unit derived from a carboxyl group-containing vinyl monomer.
[0149] The polymerization method of the monomer containing (meth)acrylate ester is not particularly limited, and examples thereof include known polymerization methods. For example, the monomer containing (meth)acrylate ester and a polymerization initiator are added to water to polymerize the monomer containing (meth)acrylate ester.
[0150] The polymerization initiator is not particularly limited, and examples thereof include hydrogen peroxide; persulfates such as ammonium persulfate, potassium persulfate, and sodium persulfate; organic peroxides such as cumene hydroperoxide, tert-butyl hydroperoxide, benzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl perbenzoate, and lauroyl peroxide; azo compounds such as azobisisobutyronitrile; redox initiators obtained by combining oxidants such as hydrogen peroxide, persulfates, organic peroxides, or azo compounds with substances that generate metal ions such as iron ions, sodium bisulphite, formaldehyde, sodium pyrosulfite, sodium bisulfite, L-ascorbic acid, or reducing agents such as Rongalite, etc. These polymerization initiators may be used alone or in combination of two or more.
[0151] The amount of the polymerization initiator used can be appropriately set depending on the purpose and application, and is, for example, 0.1% by mass or more and 5% by mass or less based on the total amount of monomers including (meth)acrylate used for producing the acrylic polymer (B).
[0152] Furthermore, during the polymerization of the monomer containing the (meth)acrylate ester, a molecular weight modifier may be added as needed.
[0153] As the molecular weight modifier, for example, thiols such as tert-dodecyl mercaptan and n-dodecyl mercaptan; allyl compounds such as allyl sulfonic acid and methacrylic acid or sodium salts of these allyl compounds can be cited. These molecular weight modifiers can be used alone or in combination of two or more. The amount of the molecular weight modifier added can be appropriately set according to the purpose and use.
[0154] The polymerization of the monomer containing (meth)acrylate is usually carried out under normal pressure. The polymerization temperature of the monomer containing (meth)acrylate is, for example, 30°C or more, preferably 50°C or more, for example, 95°C or less, preferably 85°C or less. The polymerization time of the monomer containing (meth)acrylate is, for example, 1 hour or more, preferably 2 hours or more, for example, 30 hours or less, preferably 20 hours or less.
[0155] When the monomer containing a (meth)acrylate is polymerized, an emulsifier (surfactant) may be added as needed from the viewpoint of improving polymerization stability.
[0156] Examples of the emulsifier include anionic surfactants, nonionic surfactants, and cationic surfactants.
[0157] Examples of the anionic surfactant include sodium dodecylbenzenesulfonate, sodium lauryl sulfate, sodium alkyl diphenyl ether disulfonate, sodium alkyl naphthalene sulfonate, sodium dialkyl sulfosuccinate, sodium stearate, potassium oleate, sodium dioctyl sulfosuccinate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkyl phenyl ether sulfate, sodium dialkyl sulfosuccinate, sodium stearate, sodium oleate, and sodium salt of tert-octylphenoxyethoxypolyethoxyethyl sulfate.
[0158] Examples of the nonionic surfactant include polyoxyethylene lauryl ether, polyoxyethylene octylphenyl ether, polyoxyethylene oleyl phenyl ether, polyoxyethylene nonylphenyl ether, oxyethylene-oxypropylene block copolymers, tert-octylphenoxyethylpolyethoxyethanol, and nonylphenoxyethylpolyethoxyethanol.
[0159] Examples of the cationic surfactant include lauryltrimethylammonium chloride and stearyltrimethylammonium chloride.
[0160] Among these emulsifiers, anionic surfactants are preferred, and sodium dodecylbenzenesulfonate is more preferred.
[0161] These emulsifiers may be used alone or in combination of two or more.
[0162] The addition ratio of the emulsifier is not particularly limited, but is, from the viewpoint of stability when the composite particles (D) are produced by the method described later, for example, 0.02% by mass or more and, for example, 5% by mass or less relative to the total amount of monomers containing (meth)acrylate used to produce the acrylic polymer (B).
[0163] When the monomer containing (meth)acrylate is polymerized, additives such as a pH adjuster and a metal ion sealing agent such as ethylenediaminetetraacetic acid or a salt thereof may be added at an appropriate ratio from the viewpoint of improving polymerization stability.
[0164] The weight average molecular weight of the acrylic polymer (B) is, for example, 5,000 or more, preferably 10,000 or more, and for example, 1,000,000 or less, preferably 500,000 or less, in terms of standard polystyrene measured by gel permeation chromatography (GPC).
[0165] The glass transition temperature of the acrylic polymer (B) is, for example, -28°C or higher, preferably -10°C or higher, for example, 80°C or lower, preferably 60°C or lower. When the glass transition temperature of the acrylic polymer (B) is within the above range, composite particles (D) having excellent adhesive strength and blocking resistance can be obtained.
[0166] From the viewpoint of achieving improvement in adhesive strength, the glass transition temperature of the acrylic polymer (B) is preferably 20° C. or lower, more preferably 10° C. or lower.
[0167] From the viewpoint of improving the blocking resistance, the glass transition temperature of the acrylic polymer (B) is preferably higher than 0° C., and more preferably higher than 10° C. The glass transition temperature of the acrylic polymer (B) can be set to a desired value by, for example, adjusting the combination of the above-mentioned monomers, the content ratio of the monomers, the weight average molecular weight, etc.
[0168] <Composite Particles (D)>
[0169] The composite particles (D) contain the above-mentioned ethylene-unsaturated carboxylic acid copolymer mixture (A) and the acrylic polymer (B). As long as the composite particles (D) contain the above-mentioned ethylene-unsaturated carboxylic acid copolymer mixture (A) and the acrylic polymer (B), there is no particular limitation on their form, and examples thereof include core / shell structures, composite structures, localized structures, spherical structures, octopus structures, raspberry structures, multi-particle composite structures, and IPN structures.
[0170] Particularly preferred is a structure in which a phase composed of an acrylic polymer (B) is dispersed in a continuous phase of an ethylene-unsaturated carboxylic acid copolymer mixture (A).
[0171] The method for producing such composite particles (D) is not particularly limited, and the composite particles (D) can be produced, for example, by the following methods (1) to (3). It should be noted that two or more ethylene-unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids can be produced separately by the above methods, or the two or more ethylene-unsaturated carboxylic acid copolymers can be obtained as commercial products.
[0172] Method (1): A method for producing composite particles (D) comprising the following steps:
[0173] A step of mixing two or more ethylene-unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids and, if necessary, an olefin resin (c) to prepare an ethylene-unsaturated carboxylic acid copolymer mixture (A); and
[0174] A step of polymerizing a monomer containing a (meth)acrylic acid ester in the presence of the mixture (A) by the above-mentioned method to produce an acrylic polymer (B).
[0175] Method (2): A method for producing composite particles (D) comprising the following steps:
[0176] A step of emulsifying an ethylene-unsaturated carboxylic acid copolymer mixture (A) comprising two or more ethylene-unsaturated carboxylic acid copolymers having different contents of a structural unit derived from an unsaturated carboxylic acid and, if necessary, an olefin-based resin (c) in the presence of water to obtain a dispersion 1; and
[0177] A step of adding a monomer containing a (meth)acrylic acid ester to the above-mentioned dispersion 1 in the presence of a polymerization initiator to polymerize the acrylic polymer (B) to obtain a dispersion 2 containing composite particles (D) having an ethylene-unsaturated carboxylic acid copolymer mixture (A) and the acrylic polymer (B).
[0178] Method (3): A method for producing composite particles (D) comprising the following steps:
[0179] A step of polymerizing a monomer containing a (meth)acrylate ester by the above method to prepare an acrylic polymer (B);
[0180] A step of producing two or more ethylene-unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids by the above method in the presence of the obtained acrylic polymer (B) (for example, an aqueous dispersion of the acrylic polymer (B)); and
[0181] Furthermore, a step of adding an olefin-based resin (c) as necessary.
[0182] Among these methods (1) to (3), method (2) is preferred from the viewpoint of being able to reliably produce composite particles (D) having desired properties.
[0183] It should be noted that, as for the specific conditions and methods of the step of obtaining the dispersion 1, the conditions and methods described for the production of the ethylene-unsaturated carboxylic acid copolymer mixture (A), in particular, the conditions and methods described for the production of the aqueous dispersion of the ethylene-unsaturated carboxylic acid copolymer mixture (A) can be applied. In addition, as for the specific conditions and methods of the step of obtaining the dispersion 2 for the polymerization of the acrylic polymer (B), the conditions and methods described for the polymerization of the acrylic polymer (B), in particular, the conditions and methods of the step of adding a monomer containing a (meth) acrylic acid ester and a polymerization initiator to water and polymerizing the monomer containing a (meth) acrylic acid ester can be applied.
[0184] The content of the ethylene-unsaturated carboxylic acid copolymer mixture (A) in the composite particles (D) is preferably from 20% by mass to 80% by mass, and more preferably from 30% by mass to 75% by mass.
[0185] The content of the acrylic polymer (B) in the composite particles (D) is preferably 20% by mass or more and 80% by mass or less, and more preferably 25% by mass or more and 70% by mass or less.
[0186] When the contents of the ethylene-unsaturated carboxylic acid copolymer mixture (A) and the acrylic polymer (B) in the composite particles (D) are within the above ranges, composite particles (D) having excellent adhesive strength can be obtained.
[0187] The contents of the ethylene-unsaturated carboxylic acid copolymer mixture (A) and the acrylic polymer (B) in the composite particles (D) can be calculated from the charging ratio of the raw material components.
[0188] When the contents of the ethylene-unsaturated carboxylic acid copolymer mixture (A) and the acrylic polymer (B) are within the above ranges, composite particles (D) having excellent adhesive strength can be obtained.
[0189] The weight average particle size (measurement method: light scattering measurement) of the composite particles (D) is, for example, 10 nm or more, for example, 10 μm or less, and preferably 1 μm or less.
[0190] The volume average particle size of the composite particles (D) observed by an electron microscope is, for example, 50 nm or more, preferably 60 nm or more, more preferably 80 nm or more, and for example, 300 nm or less, more preferably 200 nm or less, further preferably 120 nm or less.
[0191] When the average particle size is within the above range, the storage stability of the aqueous dispersion of the composite particles (D) can be improved, and the transparency and water resistance of the laminate (described later) can be improved.
[0192] Furthermore, the water dispersion obtained by the present invention may contain additives in addition to the above-mentioned resin component.
[0193] As additives, for example, the above-mentioned emulsifier, curing agent, cross-linking agent, film-making aid, defoamer, anti-cratering agent, leveling agent, tackifier, hardness imparting agent, preservative, thickener, antifreeze agent, dispersant, inorganic pigment, organic pigment etc. can be enumerated. These additives can be used alone or in combination of two or more. The addition amount of these additives and the period of addition etc. can be suitably set according to purpose and use.
[0194] The solid content concentration of the aqueous dispersion obtained by the present invention is, for example, 10% by mass or more, preferably 20% by mass or more, for example, 60% by mass or less, preferably 50% by mass or less. It should be noted that the so-called solid content of the aqueous dispersion is the component containing the resin component remaining when the volatile components of the aqueous dispersion are removed by heating or the like.
[0195] The pH of the aqueous dispersion obtained by the present invention is, for example, 7 or more, preferably 8 or more, and for example, 11 or less, preferably 10 or less.
[0196] The aqueous dispersion obtained by the present invention can be suitably used to form an adhesive layer (heat seal layer) of a laminate. The laminate having the adhesive layer has excellent adhesive strength. Therefore, the aqueous dispersion of the present invention is suitable as an adhesive composition.
[0197] The laminate of the present invention comprises a substrate and an adhesive layer laminated on at least one surface of the substrate.
[0198] The adhesive layer comprises the composite particles (D) having an ethylene-unsaturated carboxylic acid copolymer mixture (A) and an acrylic polymer (B).
[0199] The ethylene-unsaturated carboxylic acid copolymer mixture (A) comprises two or more ethylene-unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids. The laminate may have other layers as long as it has the adhesive layer comprising the substrate and the composite particles (D).
[0200] The adhesive layer of the laminate is obtained, for example, by drying a coating of the aqueous dispersion obtained in the present invention.
[0201] In the laminate of the present invention, the adhesive layer may be present on one side of the substrate or on both sides of the substrate. In addition, the adhesive layer may be present on the entire surface of the substrate or on a part of the substrate.
[0202] Examples of the substrate include cellophane, polyethylene, ethylene-vinyl acetate copolymers, ionomers, polypropylene, polyamide (nylon), polyesters such as polyethylene terephthalate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymers, polycarbonate, polystyrene, polyacrylonitrile copolymers, and mixtures thereof; plastic films formed from plastic materials such as cellophane, polyethylene, ethylene-vinyl acetate copolymers, ionomers, polypropylene, polyamide (nylon), polyesters such as polyethylene terephthalate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymers, polycarbonate, polystyrene, polyacrylonitrile copolymers, and mixtures thereof; vapor-deposited films obtained by vapor-depositing metals such as aluminum, gold, silver, copper, nickel, zinc, titanium, cobalt, indium, chromium, or inorganic oxides such as aluminum oxide and silicon oxide onto these plastic films; metal foils such as aluminum foil, paper, nonwoven fabrics, and the like.
[0203] There are no particular restrictions on the paper that can be used as the base material of the laminate, and known paper containing pulp as the main component can be used. Examples of the pulp that can be used as the main component of paper include chemical pulps such as LBKP (bleached kraft pulp of broadleaf trees) and NBKP (bleached kraft pulp of coniferous trees); mechanical pulps such as GP (groundwood), PGW (pressure groundwood), RMP (refiner mechanical pulp), TMP (thermomechanical pulp), CTMP (chemical thermomechanical pulp), CMP (chemical mechanical pulp), and CGP (chemical fine grinding pulp); wood pulps such as DIP (deinked pulp); non-wood pulps such as kenaf, bagasse, bamboo, and cotton; and the like.
[0204] These may be used alone or in combination of two or more. For example, pulp containing 90 to 100% by mass of LBKP (bleached kraft pulp) may be used as the pulp.
[0205] Furthermore, the pulp may contain synthetic fibers within a range not impairing the effects of the present invention.
[0206] From the viewpoint of environmental protection, among the pulps, ECF (Elemental Chlorine Free) pulp, TCF (Total Chlorine Free) pulp, waste paper pulp, and pulp obtained from plantations are preferred.
[0207] The pulp beating degree is, for example, 200 to 700 ml CSF, preferably 450 to 620 ml CSF, in terms of Canadian Standard Freeness (JIS P 8121: 1995 "Test method for freeness of pulp").
[0208] As the paper used as the substrate, paper containing fillers may also be used. Examples of fillers include light calcium carbonate, heavy calcium carbonate, talc, clay, kaolin, calcined clay, titanium dioxide, and aluminum hydroxide. The filler content in the paper is, for example, 1 to 30 parts by mass relative to 100 parts by mass of the dry mass of the pulp. When light calcium carbonate is included as a filler, for example, 1 to 10 parts by mass of light calcium carbonate may be included relative to 100 parts by mass of the dry mass of the pulp.
[0209] In addition, the aforementioned paper may contain various known papermaking additives in addition to pulp. Examples of papermaking additives include internal paper strength enhancers such as sizing agents and wet paper strength enhancers; expanders, yield enhancers, filterability enhancers, coloring dyes, coloring pigments, fluorescent brighteners, fluorescent decolorizers, and pitch controllers.
[0210] Furthermore, the paper used as the substrate may be paper coated with a water-soluble polymer such as starch, polyvinyl alcohol, or polyacrylamide.
[0211] The papermaking method of the paper serving as the substrate is not particularly limited, and the paper can be manufactured by various papermaking machines such as a fourdrinier papermaking machine, a fourdrinier multilayer papermaking machine, a cylinder papermaking machine, a cylinder multilayer papermaking machine, a fourdrinier cylinder combination multilayer papermaking machine, and a sandwich papermaking machine. In addition, the paper used in the laminate of the present invention may be a single-layer papermaking machine, a multi-layer papermaking machine, or a multi-layer laminated product.
[0212] From the viewpoint that the heat sealability of the adhesive layer included in the laminate is more excellent, among these substrates, metal foil is preferred, and aluminum foil is more preferred.
[0213] These substrates may be used alone or in combination of two or more.
[0214] The adhesive layer contained in the laminate of the present invention can be obtained, for example, by coating (applying) an aqueous dispersion containing composite particles (D) obtained in the present invention on at least one surface of the aforementioned substrate, drying the layer formed by the coating, and removing volatile components such as water contained in at least a portion of the aforementioned aqueous dispersion.
[0215] There are no particular restrictions on the coating (application) method of the aqueous dispersion obtained in the present invention, and examples thereof include die coating, flow coating, spray coating, rod coating, gravure coating, gravure reverse coating, kiss reverse coating, micro gravure coating, roll coating, knife coating, rod coating, roll knife coating, air knife coating, comma roll coating, reverse roll coating, transfer roll coating, kiss roll coating, curtain coating, and printing.
[0216] The drying conditions for the layer formed from the applied material of the aqueous dispersion are not particularly limited as long as volatile components such as water from the aqueous dispersion can be removed. The drying temperature is, for example, 100 to 200° C. and the drying time is, for example, 10 seconds to 30 minutes.
[0217] The thickness of the adhesive layer may be appropriately set depending on the intended use, and is, for example, 0.2 μm or more, preferably 1 μm or more, and, for example, 100 μm or less, preferably 20 μm or less.
[0218] In order to improve the adhesion between the substrate and the adhesive layer in the laminate, the substrate may be subjected to pretreatment such as primer (titanate, polyethyleneimine, etc.), corona discharge treatment, or chemical conversion treatment before the adhesive layer is provided.
[0219] When paper is used as the substrate of the laminate of the present invention, one or more coating layers may be provided in addition to the adhesive layer. Examples of the coating layer include a pigment coating layer obtained from a coating liquid containing a pigment and an adhesive.
[0220] As the pigment contained in the pigment coating layer, known pigments used in the coating layer of conventional coated paper for printing can be used, and examples thereof include inorganic pigments such as calcium carbonate (heavy calcium carbonate, light calcium carbonate, etc.), kaolin (including clay), calcined clay, talc, magnesium carbonate, barium sulfate, calcium sulfate, titanium dioxide, zinc oxide, zinc sulfate, zinc carbonate, calcium silicate, aluminum silicate, magnesium silicate, diatomaceous earth, aluminum hydroxide, and magnesium hydroxide; and organic pigments (so-called plastic pigments) such as acrylic resins, styrene resins, vinyl chloride resins, nylon, and resins obtained by copolymerizing monomers constituting these resins.
[0221] As the pigment used in the pigment coating layer, for example, a combination of 20 to 40 parts by mass of kaolin and 60 to 80 parts by mass of heavy calcium carbonate can be used.
[0222] In addition, as the adhesive used in the pigment coating layer, known adhesives used in the coating layer of conventional coated printing paper can also be used, and examples thereof include starches such as butadiene copolymer latex, crosslinker-modified starch, oxidized starch, enzyme-modified starch, esterified starch, etherified starch, cationic starch, and amphoteric starch; water-soluble polymers such as gelatin, casein, soy protein, and polyvinyl alcohol; and synthetic resins such as vinyl acetate, ethylene vinyl acetate, polyurethane resins, acrylic resins, polyester resins, and polyamide resins.
[0223] The mixing ratio of the pigment and the adhesive in the pigment coating layer is not particularly limited, but preferably the adhesive is 5 to 50 parts by mass relative to 100 parts by mass of the pigment. For example, a combination of 1 to 5 parts by mass of phosphated starch and 5 to 15 parts by mass of styrene butadiene latex adhesive relative to 100 parts by mass of the pigment can be used.
[0224] The pigment coating layer may contain various auxiliary agents as long as the effects of the present invention are not impaired, for example, a viscosity modifier, a softener, a gloss imparting agent, a water resistance agent, a dispersant, a flow modifier, an ultraviolet absorber, a stabilizer, an antistatic agent, a cross-linking agent, a sizing agent, a fluorescent whitening agent, a colorant, a pH adjuster, a defoaming agent, a plasticizer, and a preservative.
[0225] The coating amount of the coating liquid for forming such a pigment coating layer is, for example, 2 to 40 g / m2 in terms of solid content per side of the base paper. 2 .
[0226] As one embodiment of the laminated body with paper as the base material (for example, packaging paper) of the present invention, the adhesive layer obtained from the aqueous dispersion of the present invention can be arranged on the aforementioned pigment coating layer arranged on the paper. As another embodiment, the pigment coating layer can also be arranged only on one side of the paper, and the aforementioned adhesive layer can be arranged on the other side where the pigment coating layer is not arranged.
[0227] In the laminate of the present invention, there is an adhesive layer containing composite particles (D). The adhesive layer has excellent heat sealing strength. In addition, the adhesive layer contained in the laminate of the present invention is usually made of an aqueous dispersion having composite particles (D). When the adhesive layer is made from the aqueous dispersion, the amount of organic solvent remaining in the adhesive layer is small, and the amount of residual organic solvent in the aforementioned adhesive layer can be set to preferably 100 ppm or less, more preferably 10 ppm or less.
[0228] The laminate obtained in the present invention can be suitably used as a heat-sealing material in various industrial fields.
[0229] By heat sealing, the substrate and the adherend layer included in the laminate of the present invention are attached via the adhesive layer. The adherend layer may be included in the laminate of the present invention, or may be a layer included in an article separate from the laminate of the present invention.
[0230] Specific examples of the adherend layer include the same materials as those used for the base material included in the laminate, such as plastic films, vapor-deposited films, metal foils, papers, and nonwoven fabrics.
[0231] From the viewpoint that the heat-sealability of the adhesive layer included in the laminate is more excellent, among these substrates, a plastic film is preferred, and a plastic film made of polyvinyl chloride, polyvinylidene chloride, or a mixture thereof is more preferred.
[0232] These adherend layers may be used alone or in combination of two or more.
[0233] In addition, the laminate of the present invention can also be a laminate comprising the aforementioned adherend layer in addition to the substrate and the adhesive layer. In this case, the substrate and the adherend layer can be pasted via the adhesive layer. When pasted, in the laminate of the present invention, the adherend layer is laminated on the surface opposite to the surface in contact with the substrate of the aforementioned adhesive layer.
[0234] There is no particular limitation on the method for heat-sealing the substrate and the adherend layer. For example, the substrate and the adherend layer included in the laminate may be superimposed via an adhesive layer and then heated and pressurized to perform heat sealing.
[0235] In addition, when the adherend layer further has an adhesive layer (2) containing the composite particles (D), the adhesive layer contained in the laminate of the present invention can be superimposed on the adhesive layer (2) and then heated and pressurized to perform heat sealing.
[0236] The heating temperature during heat sealing is, for example, 80° C. or more, preferably 100° C. or more, for example, 250° C. or less, preferably 200° C. or less. The pressure during heat sealing is, for example, 50 kPa or more, preferably 100 kPa or more, for example, 500 kPa or less, preferably 300 kPa or less.
[0237] The adhesive strength between the substrate and the adherend layer included in the laminate of the present invention can be evaluated by the peel strength between the substrate and the adherend layer. 2 The peel strength between the substrate and the adherend layer when peeled at 180 degrees after 0.5 seconds of thermocompression bonding under the conditions of is preferably 8N or more.
[0238] It should be noted that a laminate obtained by laminating an adherend layer on at least one surface of an adhesive layer contained in the laminate as described above (in other words, a laminate obtained by laminating an adherend layer on at least one surface of an adhesive layer contained in the laminate) is included in the laminate of the present invention, regardless of its heat-sealed state (i.e., before and after heat sealing).
[0239] The laminate obtained in the present invention is excellent in heat-sealing strength and can therefore be suitably used as a packaging material in various industrial fields.
[0240] The packaged articles to be packaged using the packaging material comprising the laminate of the present invention are not particularly limited, and examples thereof include foods such as snacks, tea, and condiments; aromatics such as tobacco and fragrant wood; and various industrial products such as pharmaceuticals and paper.
[0241] The packaging material including the laminate of the present invention has excellent heat seal strength. Therefore, it is expected that the heat-sealed packaged object can be inhibited from deteriorating. In addition, when the aqueous dispersion of the present invention is used to prepare an adhesive layer, the burden on the environment is small.
[0242] Example
[0243] Hereinafter, the present invention will be described in detail with reference to Examples and Comparative Examples, but the present invention is not limited thereto.
[0244] The polymers used in Examples 1-1 to 1-13 and Comparative Examples 1-1 to 1-3 are as follows.
[0245] Ethylene·unsaturated carboxylic acid copolymer (a1-1): EMAA (ethylene·methacrylic acid copolymer); content of structural units derived from ethylene: 80% by mass, content of structural units derived from methacrylic acid: 20% by mass
[0246] Ethylene·unsaturated carboxylic acid copolymer (a1-2): EMAA; content of structural units derived from ethylene: 85% by mass, content of structural units derived from methacrylic acid: 15% by mass
[0247] Ethylene·unsaturated carboxylic acid copolymer (a1-3): EAA (ethylene·acrylic acid copolymer); content of structural units derived from ethylene: 82% by mass, content of structural units derived from acrylic acid: 18% by mass
[0248] Ethylene·unsaturated carboxylic acid copolymer (a2-1): EMAA; content of structural units derived from ethylene: 90% by mass, content of structural units derived from methacrylic acid: 10% by mass
[0249] Ethylene·unsaturated carboxylic acid copolymer (a2-2): EMAA; content of structural units derived from ethylene: 92% by mass, content of structural units derived from methacrylic acid: 8% by mass
[0250] Ethylene·unsaturated carboxylic acid copolymer (a2-3): EMAA; content of structural units derived from ethylene: 96% by mass, content of structural units derived from methacrylic acid: 4% by mass
[0251] Olefin polymer (c-1): EVA (ethylene-vinyl acetate copolymer); content of structural units derived from ethylene: 72% by mass, content of structural units derived from vinyl acetate: 28% by mass
[0252] Olefin polymer (c-2): EBR (ethylene-1-butene copolymer); content of structural units derived from ethylene: 93 mol%
[0253] Olefin polymer (c-3): LDPE (low-density polyethylene); density 918 kg / m 3
[0254] The monomers used for preparing the acrylic polymer in each of the Examples and Comparative Examples described in Tables 1 and 2 are as follows.
[0255] MMA: Methyl Methacrylate
[0256] nBMA: n-butyl methacrylate
[0257] nBA: n-butyl acrylate
[0258] ST: Styrene
[0259] (Example 1-1)
[0260] 50 parts by mass of ethylene·unsaturated carboxylic acid copolymer (a1-1), 25 parts by mass of ethylene·unsaturated carboxylic acid copolymer (a1-2), and 25 parts by mass of ethylene·unsaturated carboxylic acid copolymer (a2-1) were charged into a single-screw extruder and melt-kneaded at 150°C to obtain 100 parts by mass of a resin mixture.
[0261] 100 parts by mass of the obtained resin mixture, 6.3 parts by mass of a 48% by mass potassium hydroxide aqueous solution, and 158 parts by mass of deionized water were placed in a reaction vessel 1, heated to 150° C. under a nitrogen stream while stirring, and maintained at 150° C. for 4 hours under stirring conditions to obtain a raw material water dispersion (α1) of an ethylene·unsaturated carboxylic acid copolymer mixture (A-1) containing three kinds of ethylene·unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids. The neutralization degree of the obtained raw material water dispersion (α1) was measured by the following method.
[0262] Next, 278 parts by mass of the obtained raw material aqueous dispersion (α1) containing the mixture (A-1) and 80 parts by mass of deionized water were charged into another reaction container 2, the temperature was raised to 80° C. under a nitrogen flow, and 0.3 parts by mass of potassium persulfate (polymerization initiator) was added.
[0263] Separately, 79 parts by mass of n-butyl methacrylate, 21 parts by mass of n-butyl acrylate, 0.2 parts by mass of n-dodecyl mercaptan (molecular weight modifier), and 0.4 parts by mass of sodium dodecylbenzenesulfonate (emulsifier) were added and emulsified in 40 parts by mass of deionized water to obtain an emulsified mixture (β-1).
[0264] The obtained emulsified mixture (β-1) was added dropwise to a reaction vessel 2 maintained at 80°C over 2 hours, and further maintained at 80°C for 2 hours to complete the polymerization reaction, and then the polymerization reaction was stopped. Thus, an acrylic polymer (B-1) containing a structural unit derived from a (meth)acrylate was prepared, and an aqueous dispersion containing composite particles (D-1) having an ethylene·unsaturated carboxylic acid copolymer mixture (A-1) and an acrylic polymer (B-1) was obtained. The degree of neutralization of the ethylene·unsaturated carboxylic acid copolymer mixture (A-1), the polymerization stability during the preparation of the aqueous dispersion, and the storage stability of the obtained aqueous dispersion were evaluated by the following method.
[0265] (Examples 1-2 to 1-8 and Comparative Examples 1-1 to 1-3)
[0266] In Examples 1-2 to 1-8 and Comparative Examples 1-1 to 1-3, the type and amount of the ethylene-unsaturated carboxylic acid copolymer used were changed as described in Tables 1 and 2, the amount of potassium hydroxide and the amount of deionized water added were changed so as to achieve the neutralization degree and solid content concentration described in Tables 1 and 2, and the type and amount of the monomer used to produce the acrylic polymer (B) were changed as described in Tables 1 and 2. In the same manner as in Example 1-1, a raw material aqueous dispersion of an ethylene-unsaturated carboxylic acid copolymer mixture (in Comparative Examples 1 to 3, a raw material aqueous dispersion of an ethylene-unsaturated carboxylic acid copolymer) and an acrylic polymer were polymerized to produce an aqueous dispersion containing composite particles. The degree of neutralization of the ethylene-unsaturated carboxylic acid copolymer mixture or the ethylene-unsaturated carboxylic acid copolymer contained in the raw dispersion, the polymerization stability during the preparation of the aqueous dispersion, and the storage stability of the obtained aqueous dispersion were evaluated by the following method.
[0267] (Examples 1-9 to 1-13)
[0268] In Examples 1-9 to 1-13, the types and addition amounts of the ethylene-unsaturated carboxylic acid copolymer (a) and the olefin polymer (c) contained in the ethylene-unsaturated carboxylic acid copolymer mixture (A-1) were changed as described in Table 2, and the addition amounts of potassium hydroxide and deionized water were changed so as to achieve the neutralization degree and solid content concentration described in Tables 1 and 2. In the same manner as in Example 1-1, melt kneading was performed to prepare 100 parts by mass of a resin mixture, and the acrylic polymer was polymerized in the same manner as in Example 1-1, except that the types and addition amounts of the monomers used to produce the acrylic polymer (B) were changed as described in Table 2, to prepare an aqueous dispersion containing composite particles. The degree of neutralization of the ethylene-unsaturated carboxylic acid copolymer mixture contained in the raw dispersion, the polymerization stability during the preparation of the aqueous dispersion, and the storage stability of the obtained aqueous dispersion were evaluated by the following methods.
[0269] <Neutralization degree>
[0270] The neutralization degree of the whole ethylene / unsaturated carboxylic acid copolymer mixture or the ethylene / unsaturated carboxylic acid copolymer used in each of Examples 1-1 to 1-13 and Comparative Examples 1-1 to 1-3 was measured as follows.
[0271] A coating film was prepared from the aqueous dispersion obtained in each example and comparative example, and the infrared absorption spectrum of the coating film was measured using a Fourier transform infrared spectrophotometer (FT-IR) to determine the 1700 cm-1 wavelength attributable to the carboxyl group. -1 The peak height of the absorption is taken as the peak height a.
[0272] The ethylene-unsaturated carboxylic acid copolymer mixture used in the examples or the ethylene-unsaturated carboxylic acid copolymer used in the comparative examples was brought into contact with hydrochloric acid to remove (demetallize) the metal ions contained in the resin component of the aqueous dispersion, thereby obtaining an ethylene-unsaturated carboxylic acid copolymer containing no metal ions. The same sample as above was prepared from the copolymer, and the infrared absorption spectrum was measured in the same manner to obtain the infrared absorption spectrum at 1700 cm -1 The peak height of the absorption is taken as the peak height b.
[0273] From these obtained values, the degree of neutralization (%) was calculated by the following formula.
[0274] Neutralization degree (%) = 100-100 × (peak height a) / (peak height b)
[0275] It should be noted that the peak height a corresponds to the number of carboxyl groups not bonded to metal ions in the copolymer mixture or copolymer, and the peak height b corresponds to the number of all carboxyl groups contained in the copolymer mixture or copolymer.
[0276] <Polymerization Stability>
[0277] The state of the water dispersion of the composite particles after polymerization of the acrylic polymer in Examples 1-1 to 1-13 and Comparative Examples 1-1 to 1-3 was evaluated according to the following criteria. The amount of aggregates was determined by the following method.
[0278] ◎: Agglutination amount less than 500ppm
[0279] ○: The amount of aggregates was 500 ppm or more and less than 2000 ppm, and the fluidity was maintained.
[0280] △: The amount of coagulated matter was 2000 ppm or more and a large amount was generated, but the fluidity of the liquid was maintained.
[0281] ×: A large amount of coagulation was generated, and the fluidity of the liquid was lost.
[0282] (Method for measuring the amount of aggregates)
[0283] About 100 g of the water dispersion of the composite particles obtained in the above-mentioned examples and comparative examples was weighed, and the mass of the water dispersion was measured (a (g)). The mass of a stainless steel mesh (Φ51 mm × 300 mesh) was measured in advance (b (g)), and the weighed water dispersion was filtered using the stainless steel mesh, and the filtrate was dried together with the stainless steel mesh at 150° C. for 40 minutes, and then allowed to cool, and the mass of the dried sieve and filtrate was measured (c (g)).
[0284] From these measured values, the amount of aggregate (ppm) was calculated using the following formula.
[0285] Amount of aggregates (ppm) = (cb) × 1,000,000 / a
[0286] <Storage stability>
[0287] The dispersions of the composite particles obtained in the above Examples and Comparative Examples were stored at 40° C. for 3 months, and the state of the aqueous dispersions after storage was evaluated according to the following criteria.
[0288] ◎: No liquid separation.
[0289] ×: The liquid separated into two layers, and a layer of solid matter was generated on the upper part of the liquid.
[0290] [Table 1]
[0291]
[0292] [Table 2]
[0293]
[0294] The base films used in Examples 2-1 to 2-10 described in Table 3 below are as follows.
[0295] AL: Hard aluminum foil (thickness: 20μm)
[0296] Paper: Single gloss kraft paper (weight: 80g / m 2 )
[0297] The adherend films used in the peel strength test described in Table 3 below are as follows.
[0298] AL(1): A laminated film prepared in Example 2-1, comprising a substrate film AL (hard aluminum foil) and an adhesive layer prepared from the aqueous dispersion of the composite particles (D) obtained in Example 1-1.
[0299] AL(2): A laminated film prepared in Example 2-2, comprising a base film AL and an adhesive layer prepared from the aqueous dispersion of the composite particles (D) obtained in Example 1-3.
[0300] Paper (1): A laminated film prepared in Example 2-3, having an adhesive layer prepared from the aqueous dispersion of the composite particles (D) obtained in Example 1-6 on the non-glossy surface of the substrate film paper
[0301] PVC: Polyvinyl chloride film (thickness: 200μm)
[0302] PVDC: PVC / PVDC (polyvinylidene chloride) laminated film (thickness: 320 μm; PVC thickness 250 μm + PVDC thickness 70 μm; PVDC layer is the surface overlapping with the adhesive layer)
[0303] APET: Amorphous polyethylene terephthalate film (thickness: 300 μm)
[0304] AL: Hard aluminum foil (thickness: 20μm)
[0305] (Examples 2-1 to 2-10)
[0306] <Method of applying aqueous dispersion>
[0307] The water dispersion containing the composite particles (D) obtained in the above examples described in Table 3 below was applied by a wire bar at a coating amount of 4 g / m 2 The composite particles (D) were coated on the substrate film shown in Table 3 below, and dried (drying conditions: 120° C., 15 seconds) to remove volatile components from the coated material, thereby obtaining a laminate having an adhesive layer formed of the composite particles (D) on the substrate film. It should be noted that, in the case of paper, the adhesive layer was formed on the non-glossy surface.
[0308] The obtained laminate was evaluated for transparency, substrate adhesion, blocking resistance, and peel strength by the following methods.
[0309] (Transparency)
[0310] Regarding the Examples using AL (hard aluminum foil) as the base film, the transparency of the adhesive layer composed of the composite particles (D) formed on the base film of the obtained laminate was visually evaluated in the following three stages.
[0311] ◎: Transparent
[0312] ○: Transparent but slightly cloudy
[0313] ×: Strong white turbidity
[0314] (Adhesion to substrate)
[0315] An adhesive tape was attached to the surface of the adhesive layer formed of the composite particles (D) in the laminate obtained in each example, and the degree of peeling of the adhesive layer from the base film when the adhesive tape was peeled off by hand was evaluated in the following three stages.
[0316] ◎: No peeling of the coating film or damage to the substrate (in the case of paper substrate)
[0317] ○: Partial peeling of the coating film was observed
[0318] ×: The coating is completely peeled off
[0319] (Blocking resistance)
[0320] Two square test pieces of 5×5 cm in length and width were cut out from the laminate obtained in each example. The two test pieces were stacked so that the adhesive layers formed by the composite particles (D) overlapped each other, and a pressure of 250 g / cm 2 The test pieces were left standing at 40°C for 24 hours under a load of 1000 g / cm2. After the standing, the two test pieces were peeled off and the blocking resistance was evaluated according to the following three-step criteria.
[0321] ◎: The laminated adhesive layers can be peeled off without resistance
[0322] ○: Adhesion was observed in part of the adhesive layers.
[0323] ×: Adhesion was observed over the entire surfaces of the adhesive layers.
[0324] (Peel Strength)
[0325] After the laminate obtained in each example was left at room temperature for one day and night, a short grid-shaped test film with a width of 15 mm was cut out from the laminate, and the surface of the adhesive layer formed by the composite particles (D) of the test film was superimposed on the adherend film described in the following Table 3, and the test film was subjected to a 170°C and a pressure of 2 kg / cm 2 The obtained test pieces were heat-sealed for 0.5 seconds under the conditions of , and the peel strength was measured by performing T-peeling at a tensile speed of 50 mm / sec in the examples using the laminates obtained in Examples 1-3 and 1-6 and performing 180-degree peeling at a tensile speed of 200 mm / sec in other examples.
[0326] [Table 3]
[0327]
Claims
1. A water dispersion comprising a resin component and water, wherein the resin component comprises composite particles (D) comprising an ethylene-unsaturated carboxylic acid copolymer mixture (A) and an acrylic polymer (B), The ethylene-unsaturated carboxylic acid copolymer mixture (A) comprises two or more ethylene-unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids. The ethylene-unsaturated carboxylic acid copolymer mixture (A) comprises at least one of an ethylene-unsaturated carboxylic acid copolymer (a1) having a content of structural units derived from unsaturated carboxylic acids of 12% by mass to 30% by mass, and an ethylene-unsaturated carboxylic acid copolymer (a2) having a content of structural units derived from unsaturated carboxylic acids of less than 12% by mass. The content of the ethylene-unsaturated carboxylic acid copolymer (a1) in the mixture (A) is 40% by mass or more and 80% by mass or less, and the content of the ethylene-unsaturated carboxylic acid copolymer (a2) is 20% by mass or less and 60% by mass or less, The average value of the content of the structural unit derived from the unsaturated carboxylic acid contained in the ethylene / unsaturated carboxylic acid copolymer in the ethylene / unsaturated carboxylic acid copolymer mixture (A) is 12.5 to 16.25% by mass.
2. The aqueous dispersion according to claim 1, wherein In the composite particles (D), when the total amount of (A) and (B) is 100 mass%, the content of the ethylene-unsaturated carboxylic acid copolymer mixture (A) is 20 mass% to 80 mass%, and the content of the acrylic polymer (B) is 20 mass% to 80 mass%.
3. The aqueous dispersion according to claim 1 or 2, wherein The ethylene-unsaturated carboxylic acid copolymer mixture (A) further comprises an olefin polymer (c), The total content of the ethylene-unsaturated carboxylic acid copolymer in the mixture (A) is 60% by mass or more.
4. The aqueous dispersion according to claim 3, wherein The olefin-based polymer (c) comprises at least one polymer selected from the group consisting of low-density polyethylene, ethylene·1-butene copolymer, ethylene·propylene copolymer, ethylene·1-butene·propylene copolymer, ethylene·propylene·ethylidene norbornene copolymer, ethylene·(meth)acrylate copolymer, ethylene·(meth)acrylate·unsaturated carboxylic acid copolymer, ethylene·vinyl acetate copolymer, and ethylene·vinyl acetate·carbon monoxide copolymer.
5. A method for producing the aqueous dispersion according to any one of claims 1 to 4, comprising the following steps: A step of emulsifying an ethylene-unsaturated carboxylic acid copolymer mixture (A) containing two or more ethylene-unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids in the presence of water to obtain a dispersion 1; and A step of adding a monomer containing a (meth)acrylic acid ester to the dispersion 1 in the presence of a polymerization initiator to polymerize the acrylic polymer (B) to obtain a dispersion 2 containing composite particles (D) having an ethylene-unsaturated carboxylic acid copolymer mixture (A) and the acrylic polymer (B).
6. A laminate comprising a substrate and an adhesive layer laminated on at least one surface of the substrate, The adhesive layer is obtained by drying a coating of the aqueous dispersion according to any one of claims 1 to 4.
7. The laminate according to claim 6, wherein: The adhesive layer further includes an adherend layer to be laminated on the surface opposite to the surface in contact with the substrate.
8. The laminate according to claim 6 or 7, wherein The substrate is a plastic film, a vapor-deposited film, a metal foil, paper, or a non-woven fabric.
9. The laminate according to claim 7, wherein: The adherend layer is a plastic film, a vapor-deposited film, a metal foil, paper, or a non-woven fabric.
10. The laminate according to claim 7, wherein: The adherend layer is a plastic film obtained from polyvinyl chloride, polyvinylidene chloride, or a mixture thereof.
11. A laminate comprising a substrate and an adhesive layer laminated on at least one surface of the substrate, The adhesive layer comprises composite particles (D) comprising an ethylene-unsaturated carboxylic acid copolymer mixture (A) and an acrylic polymer (B), The ethylene-unsaturated carboxylic acid copolymer mixture (A) comprises two or more ethylene-unsaturated carboxylic acid copolymers having different contents of structural units derived from unsaturated carboxylic acids. The ethylene-unsaturated carboxylic acid copolymer mixture (A) comprises at least one of an ethylene-unsaturated carboxylic acid copolymer (a1) having a content of structural units derived from unsaturated carboxylic acids of 12% by mass to 30% by mass, and an ethylene-unsaturated carboxylic acid copolymer (a2) having a content of structural units derived from unsaturated carboxylic acids of less than 12% by mass. The content of the ethylene-unsaturated carboxylic acid copolymer (a1) in the mixture (A) is 40% by mass or more and 80% by mass or less, and the content of the ethylene-unsaturated carboxylic acid copolymer (a2) is 20% by mass or less and 60% by mass or less, The average value of the content of the structural unit derived from the unsaturated carboxylic acid contained in the ethylene / unsaturated carboxylic acid copolymer in the ethylene / unsaturated carboxylic acid copolymer mixture (A) is 12.5 to 16.25% by mass.
